Male sex work in Sweden : Criminalization of the client - Bacio, Marco (Routledge, 2021)
In the late 1990s, influenced by feminist theory, Sweden became a world leader in the fight against prostitution and human trafficking. It adopted legislation that attempts to reduce prostitution, which is viewed as harmful to women, by targeting clients rather than sex workers. Clients who are charged under the legislation are subject to a fine and possible imprisonment of up to a year. However, fewer than 200 charges are brought per year, and only a small fraction of those charged are fined or imprisoned. The law has drastically reduced street prostitution (but not online prostitution) and has changed Swedish opinion about prostitution. Swedes now strongly support the legislation and believe that the sellers as well as the buyers should be punished, even though the aim of the legislation was to protect the “victims” (i.e., the sellers). The “Swedish model” has been adopted in other countries, including Norway, Iceland, France, and Ireland, though with somewhat different effects. Although the legislation deliberately excludes male sex workers on the grounds that men are not considered victims either as buyers or as sellers, it has indirectly affected men who sell sex. The goal of eliminating the sale of sex has become so widespread in Sweden that outreach to sex workers, such as giving condoms and lube and safe sex advice, is viewed as facilitating illegal encounters. Nonetheless, some private and public organizations have stepped up to provide the services that sex workers need to remain safe and healthy. Male sex workers and their clients know that they do not risk criminal charges for selling sex. Thus, the “Swedish model” not only reflects a paternalistic view of women sex workers but also gender discrimination.